Evaporation heat transfer and pressure drop in flattened microfin tubes having different aspect ratios. (January 2016) - Lee, E.J.; Kim, N.H.
Highlights: Evaporation heat transfer and pressure drop data in flattened microfin tubes using R410A. Evaporation heat transfer coefficient increases as aspect ratio increases. Pressure drop increases as aspect ratio increases. Abstract: In this study, evaporation heat transfer coefficients and pressure drops of R-410A were obtained in flattened microfin tubes (AR = 2, 4) made from 7.0 mm O.D. round microfin tubes. The test range covered mass flux 200–400 kg/m 2  s, heat flux from 5 to 15 kW/m 2 and saturation temperature from 10 to 15 °C. The evaporation heat transfer coefficient increases as mass flux or heat flux increases. The heat transfer coefficient also increases as aspect ratio increases. The frictional pressure drop increases as quality or mass flux increases, saturation temperature decreases, and is independent of heat flux. The frictional pressure drop also increases as aspect ratio increases. Comparison with existing round microfin tube correlations is made.